Análise da susceptibilidade à corrosão intergranular dos aços: AISI 317 e AISI 317L - Avelino Júnior, Archimedes Fortes (2011)
Austenitic stainless steels are known for their higher corrosion resistance and good mechanical properties at high temperatures. However, these steels are susceptible to intergranular corrosion caused by segregation of chromium carbide (M23C6) at grain boundaries. This type of corrosion is caused by the depletion of chromium in the regions adjacent to grain boundaries, making the steel as sensitized. An alternative to reduce this effect is to reduction of the carbon content in solid solution, thus decreasing the formation of carbides at high temperatures. In this work it was evaluated the resistance to sensitization of AISI 317 and AISI 317L steels from the state as received when submitted in the temperature range 400 ° C to 700 º C for different periods of time. It was also investigated a solution annealing temperature appropriate that it could minimize the sensitization effects for the material in the as received condition under the selected conditions of heat treatment. Heat treatments were performed in the time of 1h, 12h, 24h. 72h and 96h at temperatures of 400 °C, 500 ºC, 600 °C and 700 °C. Solution annealing treatments were performed at temperature of 1100ºC for 20, 60 and 240 minutes in both steel and then heat treatments were repeated under conditions where the material presented in the sensitization condition as received. After each treatment a micro structural characterization was held using both a metallurgical and a scanning electron microscope. Tests were performed with Double Loop potenciokinetic reactivation method (DL-EPR) to quantitatively assess the sensitization degree of the samples. The exposure of the samples at a temperature of 700 ° C led to the sensitization, but as received AISI 317L steel was sensitized early in comparison to the AISI 317 steel. The solution anneal heat treatment at 1100ºC was more effective in reducing the sensitization of the AISI 317L steel, showing that the time of 20 minutes is enough to improve their resistance to depletion of chromium.